2010
DOI: 10.3892/ijmm_00000422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the abrogation of TGF-β1 by antisense oligonucleotides on the expression of TGF-β-isoforms and their receptors I and II in isolated fibroblasts from keloid scars

Abstract: Abstract. Disequilibrium of dermal wound repair can result in continued accumulation of ECM and excessive scar formation. In susceptible genetically predisposed individuals, keloid formation can be observed. Keloid disease represents a benign dermal fibroproliferative tumor that is unique to humans. TGF-ß is known to play a key role in the pathogenesis of this disease which is still not fully understood. The isoforms TGF-ß1 and TGF-ß2 have profibrotic properties, whereas TGF-ß3 may have antifibrotic functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…TGF‐β exerts its function by binding to TGF‐βRI and TGF‐βRII. Moreover, TGF‐β1 regulates TGF‐βRI and TGF‐βRII expressions in an autocrine positive‐feedback fashion . In agreement with previous studies demonstrating that TGF‐β1 stimulation enhanced the expression of TGF‐β receptors in certain types of cells including human lung fibroblasts, our results also showed an increased expression of TGF‐β receptor I and II in cultured fibroblasts after TGF‐β1 treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TGF‐β exerts its function by binding to TGF‐βRI and TGF‐βRII. Moreover, TGF‐β1 regulates TGF‐βRI and TGF‐βRII expressions in an autocrine positive‐feedback fashion . In agreement with previous studies demonstrating that TGF‐β1 stimulation enhanced the expression of TGF‐β receptors in certain types of cells including human lung fibroblasts, our results also showed an increased expression of TGF‐β receptor I and II in cultured fibroblasts after TGF‐β1 treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, TGF-b1 regulates TGF-bRI and TGF-bRII expressions in an autocrine positive-feedback fashion. [45][46][47] In agreement with previous studies demonstrating that TGF-b1 stimulation enhanced the expression of TGF-b receptors in certain types of cells including human lung fibroblasts, 48,49 our results also showed an increased expression of TGF-b receptor I and II in cultured fibroblasts after TGF-b1 treatment. Addition of tacrolimus markedly inhibited the TGF-b1 enhanced TGF-bRI and TGF-bRII expressions in cultured fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has revealed that TGFβ1 and TGFβ2 were profibrotic, but TGFβ3 might be antifibrotic [16]. Because there is little information on TGFβ2 and TGFβ3 with DR, a pertinent analysis of isoforms other than TGFβ1 in this meta-analysis has not been done.…”
Section: Discussionmentioning
confidence: 99%
“…Indukowaną TGF-β1 proliferację fibroblastów keloidowych oraz syntezę kolagenu hamują również retinoidy, genisteina i takrolimus [19,80]. Innymi kierunkami modulowania ekspresji TGF-β1 w procesie gojenia ran są: śródskórna iniekcja ludzkiego rekombinowanego TGF-β3 (avotermin) -izoformy TGF-β o działaniu antyfibrotycznymoraz terapie genowe wykorzystujące antysensowe oligonukleotydy TGF-β1 i przeciwciała dla TGF-β1 [81][82][83].…”
Section: Metody Leczenia Keloidówunclassified